Syntaxonomy of ruderal vegetation of the Kuyalnyk Liman (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The present state of ruderal vegetation in the valley of the Kuyalnyk Liman is clarified, and its phytocenotic diversity is established. The largest syntaxonomic riches has the class Stellarietea mediae (13 associations, 7 alliances and 3 orders). Artemisietea vulgaris has 10 associations, 4 alliances and 2 orders and Polygono-Poetea annuae – 1 association, 1 alliance and 1 order only. The new association Amarantho blitoidis-Tribuletum terrestris are described. Agropyretum repentis, Hordeetum murini, Melilotetum albo-officinalis, Chamaeplietum officinalis, Lactucetum tataricae, Anisantho-Artemisietum austriacae, Polygonetum arenastri are most widespread associations on the investigated area. These associations are quite characteristic for the whole of Western and Eastern Europe, including Ukraine, but thermophile communities Bromo squarrosi-Sonchetum oleracei, Lactucetum tataricae, Anisantho-Artemisietum austriacae, Calamagrostietum epigei, Amarantho blitoidis-Tribuletum terrestris and Cynodontetum dactyli are present here. It is observed the increase in area and the number of ruderal communities of thermophilic annuals, due to the catastrophic reduction in recent years a water surface. Ruderal vegetation of the region is formed by synanthropic phytocoenoses and genetically previous formations of natural vegetation. There is a significant proportion of aboriginal species (up to 55 %) in floristic composition of ruderal communities. It indicates the possibility of renaturalization of natural vegetation, while reducing anthropic pressure. The wide distribution and diversity of ruderal vegetation, and its high degree adventization, testify to the threatening ecological situation in the region and a significant level of anthropic transformation of natural communities. Optimization and restoration of semi-natural and anthropic ecosystems of the Liman are necessary. The creation of the Kuyalnytskyi National Natural Park is the only solution of this problem.
Keywords: ruderal vegetation, classification of syntaxons, Kuyalnyk Liman, Ukraine.